Nature-based solutions as more-than-human art: Co-evolutionary and co-creative design approaches - Carsten Herrmann-Pillath; Simo Sarkki; Timo Maran; Katriina Soini; Juha Hiedanpää (Nature-Based Solutions, 2023)
Nature-based solutions (NbS) are mostly seen as engineering approaches to meeting challenges of human societies under ecological stress, while also nurturing biodiversity. We argue that given the accelerating speed of environmental change, NbS design for biodiversity recovery cannot be informed by past or current conditions but must create evolutionary potential for yet unknown future biodiversity. The objective of our paper is to reconceptualizing this creative role of NbS design as artwork, building on John Dewey's pragmatist aesthetics. We suggest that in emphasizing the aesthetic dimension of NbS, triggers, mechanisms and affordances can be harnessed that activate the co-creative potential of both humans and non-humans for cooperation, resilience, and future biodiversity. We build on recent developments, both practical and experimental, in interspecies art and design and locate these in the two dimensions of co-creation and co-evolution. As a result, we distinguish three categories of NbS as artwork, transformative art, interspecies art and exaptive art, present their main features and give some illustrations of how they may regenerate the current ways to approach and design NbS.